2019
DOI: 10.1016/j.pbb.2019.04.001
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the interoceptive stimulus effects of nicotine and varenicline

Abstract: Learning processes associated with nicotine influence the development of addiction to tobacco products. In the present report, we are interested in the interoceptive stimulus effects of nicotine acquiring control over appetitive behaviors-specifically, reward seeking. Also of interest is the current smoking cessation drug, varenicline (Chantix®). Varenicline, with its nicotine-like stimulus effects, can decrease withdrawal and cravings for a subset of individuals addicted to nicotine, though relapse is still c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 44 publications
1
5
0
Order By: Relevance
“…Notably, in the present study, nicotine evoked varenicline-like responding at doses that ranged from 0.05 to 0.4 mg/kg. This observation is consistent with past research reporting that the varenicline stimulus substitutes for a nicotine training stimulus across drug discrimination tasks (LeSage et al , 2009; Reichel et al , 2010; Thompson et al , 2019). However, the de Moura and McMahon (2017) study reported that nicotine did not substitute for the 3.2 mg/kg varenicline training dose.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Notably, in the present study, nicotine evoked varenicline-like responding at doses that ranged from 0.05 to 0.4 mg/kg. This observation is consistent with past research reporting that the varenicline stimulus substitutes for a nicotine training stimulus across drug discrimination tasks (LeSage et al , 2009; Reichel et al , 2010; Thompson et al , 2019). However, the de Moura and McMahon (2017) study reported that nicotine did not substitute for the 3.2 mg/kg varenicline training dose.…”
Section: Discussionsupporting
confidence: 92%
“…The initial objective of this study was to determine whether varenicline would serve as the training stimulus in the DGT task. In a set of earlier studies, we found that 1 mg/kg varenicline seamlessly replaced the control of acquired goal-tracking behavior in rats when 0.4 mg/kg nicotine initially served as the training stimulus (Thompson et al, 2019, 2020); an outcome suggesting that varenicline might serve as a training stimulus in the DGT task. The present study confirmed that possibility.…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…Supporting the latter idea, animal models such as the "discriminated goal-tracking task" show that drug interoceptive stimuli can readily guide reward-seeking behavior [22,[96][97][98][99]. In these studies, the experimenter administers either a drug (e.g., nicotine) or vehicle (e.g., saline) prior to daily conditioning sessions.…”
Section: Animal Modelsmentioning
confidence: 99%
“…If the experimental parameters are arranged in such a manner that sucrose delivery only occurs on vehicle sessions, then the opposite association can also be trained, such that rats learn to make receptacle entries on vehicle sessions and withhold receptacle entries on drug sessions [22]. Furthermore, rats previously conditioned to an interoceptive stimulus that undergo extinction sessions in which there are nonreinforced presentations of the drug interoceptive stimuli show decreases in reward-seeking behavior [97][98][99][100]. As such, understanding these learning processes may be important to consider for behavioral interventions to maintain drug abstinence.…”
Section: Animal Modelsmentioning
confidence: 99%